GONADAL AND EXTRA-GONADAL SPERM RESERVES OF KANO BROWN BUCKS AS INFLUENCED BY SEASON AND FEEDING REGIME IN SEMI-ARID ZONE OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
The study was conducted to evaluate the effect of season and feeding regime on reproductive parameters of Kano Brown bucks. A total of fourty eight (48) bucks were used for this study which comprised sixteen (16) bucks per season. At the end of this study twelve (12) bucks, three from each treatment were orchidectomised. Twenty-four right and left testes were harvested, testicular weight (g) and length (cm) were measured. Epididymis was carefully separated from the testes using scapel blade and then separated into three parts (carput, corpus and cauda epididymides) weight (g) and length (cm) were also measured. Testes and epididymis were used to determine gonadal and extra gonadal (x 106)/g/testis which was done in the laboratory. Data collected were subjected to analysis of variance using Completely Randomized Design. The results of gonadal sperm reserves (x 106)/g/testis differed significantly among the seasons, dry season recorded the highest mean value (2896.83 x106)/g/testis whereas rainy season had the lowest mean value (2350.15 x106)/g/testis. Similarly, for extra gonadal sperm reserves, dry season also recorded the highest values (1736.00 x 106) followed by harmattan season (1037.50 x 106). Based on the results of this study, it could be concluded that season and feeding regime had a significant effect on gonadal and extra gonadal sperm/spermatid reserves of Kano Brown bucks. Breeding bucks should be raised during rainy and harmattan seasons.
Keywords: Gonadal and extra-gonadal sperm reserves, Kano Brown bucks, season and feeding regime